Reflection as an Educational Strategy in Nursing Professional Development. Issue 2 (March 2015) - Miraglia, Robbin; Asselin, Marilyn E.
<x xml:space="preserve">Abstract</x> Reflection is a critical component of professional nursing practice and a strategy for learning through practice. This integrative review synthesizes the literature addressing the use of reflection as an educational strategy and reports outcomes from the use of reflective strategies. Reflection education is primarily nested in programs to meet specific clinical goals, structured with group facilitation. Findings suggest that reflective strategies stimulate learning in practice, enhance readiness to apply new knowledge, and promote practice change.